Haunted castle on Hallows Eve - Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2003)
In their magic treehouse, Jack and Annie are again transported to King Arthur$1 (Bs realm, where invisible beings, giant ravens, and mistaken magic spells have a duke$1 (Bs castle in an uproar on Halloween night.s
"A Stepping Stone book."
Keywords: Haunted houses -- Fiction; Castles -- Fiction; Ravens -- Fiction; Halloween -- Fiction; Time travel -- Fiction; Magic -- Fiction; Tree houses -- Fiction